Three new species, Xanthomonas hawaiiensis sp. nov., Stenotrophomonas aracearum sp. nov., and Stenotrophomonas oahuensis sp. nov., isolated from the Araceae family - Chuang, Shu-Cheng; Dobhal, Shefali; Alvarez, Anne M.; Arif, Mohammad (Frontiers in Microbiology, 2024)
Xanthomonas and Stenotrophomonas are closely related genera in the family Lysobacteraceae. In our previous study of aroid-associated bacterial strains, most strains isolated from anthurium and other aroids were reclassified as X. phaseoli and other Xanthomonas species. However, two strains isolated from Spathiphyllum and Colocasia were phylogenetically distant from other strains in the Xanthomonas clade and two strains isolated from Anthurium clustered within the Stenotrophomonas clade. Phylogenetic trees based on 16S rRNA and nine housekeeping genes placed the former strains with the type strain of X. sacchari from sugarcane and the latter strains with the type strain of S. bentonitica from bentonite. In pairwise comparisons with type strains, the overall genomic relatedness indices required delineation of new species; digital DNA-DNA hybridization and average nucleotide identity values were lower than 70% and 95%, respectively.Hence, three new species are proposed: S. aracearum sp. nov. and S. oahuensis sp. nov. for two strains from anthurium, and X. hawaiiensis sp. nov. for the strains from spathiphyllum and colocasia, respectively. The genome size of X. hawaiiensis sp. nov. is ~4.88 Mbp and higher than S. aracearum sp. nov. (4.33 Mbp) and S. oahuensis sp. nov. (4.68 Mbp). Gene content analysis revealed 425 and 576 core genes present in 40 xanthomonads and 25 stenotrophomonads, respectively. The average number of unique genes in Stenotrophomonas spp. was higher than in Xanthomonas spp. implying higher genetic diversity in Stenotrophomonas.